Human embryonic zeta-globin gene expression in mouse-human hybrid erythroid cell lines - Luo, Yuan Hong (My University, 1993)
Human hemoglobin (Hb) is composed of two pairs of globin chains, each of them contains a heme group. One pair of globin chain is encoded by a gene on the street arm of human chromosome 16 within the α-globin gene cluster and another pair encoded by a gene on the short arm of human chromosome 11 within the β-globin gene cluster. During human embryonic and fetal development, there are orderly changes of Hbs from embryonic to fetal, and later to adult Hbs, which are referred to as hemoglobin switching. These alterations are due to sequential activation of the globin genes in the order of their locations in chromosomes. Embryonic α-globin chains are present in abundance during the first five to six weeks of gestation. Subsequently, ζ-globin chains are supplanted by the expression of α-globin chains (Peschle et al 1985). In infants older than 3 months of age and in normal adults, ζ-globin chains are not detected by sensitive radioimmunoassays. However, exceptions were observed in a subgroup of α-thalassemia-1 carriers with a deletion of two adjacent α-globin genes while the ζ-globin gene in cis to the deletion remains intact, e.g., (--^(SEA)/) α-thalassemia-1. In adult carriers with this --^(SEA) deletion, embryonic ζ-globin chains are persistently present at a low level in their erythrocytes (Chung et al 1984, Chui et al 1986). In order to understand the mechanism leading to ζ-globin gene expression in the adult carriers with the --^(SEA) deletion, we constructed stable mouse-human somatic cell hybrids with APRT deficient murine ertythroleukemia cells bearing human chromosome 16 with either the --^(SEA) deletion or the normal α-globin gene cluster. The results showed that the human ζ-globin gene was constituitively expressed at higher levels in hybrids containing human chromosome 16 with --^(SEA) deletion than that in hybrids with the normal human chromosome 16. These observations indicate that the DNA sequences within the deletion may have a role in regulating ζ-globin gene expression. Moreover, expression of the human ζ-globin gene in cis to the deletion was readily induced by DMSO and HMBA but not butyrate, in parallel with the induction of endogenous mouse α-globin gene expression. These observations are consistent with the hypothesis that ζ-globin gene expression in the adult carriers is linked to the (--^(SRA)) deletional human chromosome 16. The ζ-globin gene in the cis to the --^(SRA) deletion can be activated by adult regulatory factors in the mouse erythroleukemia cells. It is conceivable that the ζ-globin gene is normally suppressed in the adult erythroid cells by the DNA sequences within the --^(SRA) deletion.
Keywords: Medical Sciences; Medical Sciences